PENDAMPINGAN KURSUS PENGELOLAAN DEWAN AMBALAN DALAM PENINGKATAN KEPEMIMPINAN SISWA - Ashhabul Kahfi (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
Extracurricular Scouts is a forum for fostering the leadership of upper-middle-level students consisting of Scouts. In which there is an Ambalan Council, which is filled with Enforcement Scouts who have been appointed in charge of planning, managing and mobilizing activities in the Ambalan concerned with the guidance of their supervisor. For the Kwarran program to advance the scout organization in the management of the Ambalan, each Ambalan Council must have knowledge, abilities and skills in the management of Ambalan Administration in their respective Bases. Therefore, by applying the administrative skills of the ambalan to the school administrators to prepare the Ambalan Accreditation with the learning by doing method (Learning by Doing) and the team system (Patrol System).Â Â